Fractional Reserve Banking in Islamic Finance: A Comparative Analysis of Islamic and Western Economic Perspectives - fathurrahman, Ayif (Jurnal Ar-Ribh, 2025)
This article examines the concept and implementation of fractional reserve banking (FRB) through the lens of both Western economic thought and Islamic finance. Utilizing a qualitative methodology with a library research approach, this study investigates theoretical and practical differences between the two paradigms. In conventional Western finance, FRB is widely accepted as a mechanism that enables credit expansion, supports investment, and enhances liquidity within financial systems. Economists such as Mises, Keynes, and Rothbard offer varying justifications and criticisms of this system—ranging from monetary creation efficiency to moral hazards such as artificial credit inflation. Conversely, Islamic economic thought fundamentally challenges the legitimacy of FRB due to its connection with interest (riba), risk of gharar (uncertainty), and issues of dual ownership in deposit structures. Islamic scholars argue that the practice contradicts the principles of ownership (milkiyah) and justice in financial dealings, thereby undermining the ethical framework of Sharia-compliant finance. The paper highlights how the replication of conventional banking practices in Islamic finance raises concerns about authenticity and systemic risks. Additionally, it addresses the resurgence of proposals for full-reserve banking following global financial crises, suggesting growing discontent with the status quo. Ultimately, this comparative analysis reveals a significant philosophical and operational divide between Western and Islamic views on banking and monetary policy. The study contributes to ongoing discussions about ethical financial reform and provides critical insights into the viability of implementing fractional reserve banking in Islamic financial institutions.